Optimization of lactic ferment with quinoa flour as bio-preservative alternative for packed bread - Dallagnol, Andrea Micaela (2015)
The consumers demand for food with high nutritional quality and free of chemical additives increases the need to look for new products and preservation strategies. Quinoa (Chenopodium quinoa) is an Andean pseudocereal highly appreciated because of its nutritional properties. Moreover, it is an optimal substrate for growing and production of improved amounts of antifungal compounds by Lactobacillus plantarum CRL 778. The aim of this work was to optimize a lactic ferment for packaged breads with improved nutritional value and prolonged shelf life by applying a statistical experimental design model. The addition of 30% quinoa to the wheat semi-liquid ferment (QWF) could highly improve the amino acids release (4.3 g/L) during fermentation. Moreover, this quinoa proportion was sufficient to obtain the same concentration of the antifungal compounds, phenyllactic and hydroxiphenyllactic acids (PLA and OH-PLA) as with 100% quinoa (ca. 36 and 51 mg/L, respectively). Statistical model analysis showed that citrate and skimmed milk enhanced significantly all evaluated parameters specially PLA (ca. 71 mg/L), HO-PLA (ca. 75 mg/L) and lactate (27 g/L) with a p value < 0.005. The synergic effects of higher antifungal compounds production, acids release and pH decrease allowed lowering the amount (about 50 %) of the chemical preservative calcium propionate commonly added to bread. Moreover, these breads show increased shelf life.